2010
DOI: 10.1007/s13197-010-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zero energy cool chamber and post-harvest treatments on shelf-life of fruits under semi-arid environment of Western India. Part 2. Indian gooseberry fruits

Abstract: Effect of zero energy cool chamber (ZECC) along with post-harvest treatments including CaCl 2 , mustard oil and K 2 SO 4 separately on shelf-life and fruit quality attributes of Indian gooseberry or aonla (Emblica offi cinalis Gaertn) during storage under semi-arid ecosystem of Gujarat was studied. Increase in physiological loss in weight (PLW), spoilage loss, total soluble solids, total sugar and reducing sugars, reduction in titratable acidity and ascorbic acid were observed during storage period in all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…An alternative to address this problem implies that the zero energy cool chamber (ZECC) is implementable as in its application electricity is not required, eco-friendly and low cost(M. P. Islam, Morimoto, & Hatou, 2012Md. Parvez Islam & Morimoto, 2014;Singh, Singh, Joshi, Bagle, & More, 2010;Vala, Saiyed, & Joshi, 2014). ZECC can be defined as a simple structure cooling system for vegetables and fruits storage consists of outer and inner brick walls with a filler material in between, half-ground storage space as well as a water supply system which require no electric energy(M. P. Islam et al, 2013;Md.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to address this problem implies that the zero energy cool chamber (ZECC) is implementable as in its application electricity is not required, eco-friendly and low cost(M. P. Islam, Morimoto, & Hatou, 2012Md. Parvez Islam & Morimoto, 2014;Singh, Singh, Joshi, Bagle, & More, 2010;Vala, Saiyed, & Joshi, 2014). ZECC can be defined as a simple structure cooling system for vegetables and fruits storage consists of outer and inner brick walls with a filler material in between, half-ground storage space as well as a water supply system which require no electric energy(M. P. Islam et al, 2013;Md.…”
Section: Introductionmentioning
confidence: 99%
“…The eggplants were stored in ZECC and at room temperature, resulted that with the addition of 100 l of water per day in ZECC method the shelf life enhancement reached up to 9 days. Other studies focusing on ZECC in banana (Narayana, Mustafa, & Sathiamoorthy, 2002), lemon (Prabha, H.R, A.K, & Ranjana, 2006), aonla fruit (Dhumal & Karale, 2008;Singh et al, 2010), tomato(M. P. Islam et al, , 2013Md Parvez Islam & Morimoto, 2012), grapes (Murugan, Ranjith, & Vidhya, 2011), potato (Rayaguru, Khan, & Sahoo, 2010) and apples (Sharma et al, 2010)supported that ZECC is recommended to the shelf life extension of mentioned fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…This works on the principle of evaporative cooling where reduction in temperature occurs due to evaporation of water (Lal Basediya et al, 2013). Singh et al (2010) evaluated the effect of zero energy cool chamber along with several postharvest pretreatments (CaCl 2 , mustard oil, and K 2 SO 4 ) on shelf life and quality characteristics of amla. It was observed that pretreatment of amla fruits with CaCl 2 (1.5%) and subsequent storage in zero energy cool chamber extended the shelf life up to 11 days while retaining most of the quality attributes.…”
Section: Postharvest Processing Of Amlamentioning
confidence: 99%